Sharia Compliance and Information Asymmetry for IPO In Bursa Indonesia - Afira Rohmahtunisa; Shoimatul Fitria (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyze the effect of shariah compliance status, and information asymmetry as a proxy for institutional ownership variables, and company size on excess demand in initial public offerings on the Indonesia Stock Exchange. This study uses 51 companies that conduct initial public offerings on the Indonesia Stock Exchange as research samples obtained through purposive sampling method. The research method used in this study is a quantitative method with secondary data. The analytical tool in this research is IBM SPSS version 28 using classical assumption detection in the form of normality detection, heteroscedasticity detection, autocorrelation detection, and multicollinearity detection. This study also used multiple regression analysis and hypothesis testing using t test, F test and coefficient of determination test. The results of this study show that shariah compliant status does not affect excess demand in initial public offerings, while for institutional ownership variables positively and significantly affects excess demand in initial public offerings and company size negatively and significantly affects excess demand in initial public offerings on the Stock Exchange Indonesia.